Exogenous surfactant as a component of complex non-ECMO therapy of ARDS caused by influenza A virus (2009 H1N1) - Kula, R; Maca, J; Sklienka, P; Tichy, J; Szturz, P; Jahoda, J; Czerny, D; Chylek, V; Sukenik, P (Bratislavske lekarske listy, 2011)
During the pandemy caused by novel influenza A virus (subgroup H1N1), a significant number of patients became critically ill from respiratory failure. In the most severe cases of primary pneumonia, patients develop refractory hypoxemic acute respiratory distress syndrome (ARDS) with typical computed tomographic findings of multi-lobar alveolar opacities and extremely reduced pulmonary airspace. To reduce the risk of injurious ventilation and promote survival, some authors recommend the use of extracorporeal membrane oxygenation (ECMO). Unfortunately, ECMO is expensive, associated with serious complications, and available at very few centers. Other therapeutic options are clearly needed. Here we report three patients with severe influenza pneumonia who recovered following treatment with porcine surfactant (Tab. 1, Fig. 3, Ref. 6). Full Text in free PDF www.bmj.sk.
Keywords: Influenza A Virus, H1N1 Subtype; Female; Pulmonary Surfactants; chřipka lidská; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; syndrom dechové tísně; lidé středního věku; Influenza, Human; virus chřipky A, podtyp H1N1; Middle Aged; Radiography; Respiratory Distress Syndrome; plicní surfaktanty; radiografie